Pengaruh Personality Traits Terhadap Brand Loyalty Melalui Congruity Dan Customer Satisfaction Sebagai Variabel Mediasi Pada Brand Fore Coffee - Selvia Selvia; Rodhiah Rodhiah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This studies examines the effect of personality traits on brand loyalty through congruity and customer satisfaction as a mediating variables on the brand of Fore Coffee. This research design used quantitative methods with a descriptive approach. The sampling technique used purposive sampling, with 94 respondents which all of customers from Fore Coffee. Data were collected using questionnaire. The analysis used structural equation modelling (SEM) and SmartPLS 3 as a tool for analyzing data. The results of this study indicate that personality traits have a significant positive effect on consumer congruity on the Fore Coffee’s brand, personality traits have a significant positive effect on customer satisfaction on the Fore Coffee’s brand, personality traits directly have a significant positive effect on consumer brand loyalty on the Fore Coffee’s brand, congruity have a significant positive effect on consumer satisfaction on the Fore Coffee’s brand, congruity have a significant positive effect on consumer brand loyalty in the Fore Coffee’s brand, customer satisfaction does not have a significant effect on consumer brand loyalty on the Fore Coffee’s brand, congruity mediates the influences of personality traits on consumer brand loyalty on the Fore Coffee’s brand, and customer satisfaction does not mediate the influence of personality traits on consumer brand loyalty on the Fore Coffee’s brand. Penelitian ini meneliti pengaruh personality traits terhadap brand loyalty melalui congruity dan customer satisfaction sebagai variabel mediasi pada brand Fore Coffee. Desain penelitian ini menggunakan metode kuantitatif dengan pendekatan deskriptif. Teknik pengambilan sampel menggunakan purposive sampling, dengan responden sebanyak 94 yaitu seluruh konsumen dari Fore Coffee. Teknik pengambilan data dengan menggunakan kuesioner. Analisis yang digunakan adalah structural equation modelling (SEM) dan SmartPLS 3 sebagai alat untuk menganalisis data. Hasil penelitian ini menunjukkan bahwa personality traits berpengaruh positif signifikan terhadap congruity konsumen pada brand Fore Coffee, personality traits berpengaruh positif signifikan terhadap customer satisfaction konsumen pada brand Fore Coffee, personality traits secara langsung berpengaruh positif signifikan terhadap brand loyalty konsumen pada brand Fore Coffee, congruity berpengaruh positif signifikan terhadap customer satisfaction konsumen pada brand Fore Coffee, congruity berpengaruh positif signifikan terhadap brand loyalty konsumen pada brand Fore Coffee, customer satisfaction tidak berpengaruh signifikan terhadap terhadap brand loyalty konsumen pada brand Fore Coffee, congruity memediasi pengaruh personality traits terhadap brand loyalty konsumen pada brand Fore Coffee, dan customer satisfaction tidak memediasi pengaruh personality traits terhadap brand loyalty konsumen pada brand Fore Coffee.